2006
DOI: 10.1002/cncr.21722
|View full text |Cite
|
Sign up to set email alerts
|

Uridine diphosphate glucuronosyl transferase 1A1 promoter polymorphism predicts the risk of gastrointestinal toxicity and fatigue induced by irinotecan‐based chemotherapy

Abstract: BACKGROUNDIn the current Phase II study, the authors evaluated the association between genomic polymorphic variants in uridine diphosphate glucuronosyl transferase (UGT1A1), methylenetetrahydrofolate reductase (MTHFR), and thymidylate synthase (TS) genes, and the incidence of the adverse effects of irinotecan and raltitrexed in previously heavily treated patients with metastatic colorectal carcinoma.METHODSFifty‐six patients received irinotecan (at a dose of 80 mg/m2 on Days 1, 8, 15, and 22 every 5 wks), comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
54
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(54 citation statements)
references
References 33 publications
0
54
0
Order By: Relevance
“…Patients were predominantly Caucasians in 11 trials. Four trials did not clearly report the race of the participants (16,20,22,23). The patients in these four trials, however, might have been Caucasians because these trials were conducted in Europe or America and the reported frequency of the UGT1A1*28 allele was similar to that of Caucasians.…”
Section: Study Characteristics and Methodologic Quality (Association mentioning
confidence: 98%
See 2 more Smart Citations
“…Patients were predominantly Caucasians in 11 trials. Four trials did not clearly report the race of the participants (16,20,22,23). The patients in these four trials, however, might have been Caucasians because these trials were conducted in Europe or America and the reported frequency of the UGT1A1*28 allele was similar to that of Caucasians.…”
Section: Study Characteristics and Methodologic Quality (Association mentioning
confidence: 98%
“…If the patients in a trial received different irinotecan doses and only combined toxicity-related data (or REG data) were available, we calculated the average dose. In one study (16), the numbers of chemotherapy cycles with neutropenia in each genotype group were provided instead of the number of patients. We calculated the number of patients as C × tN/tC, where C is the number of chemotherapy cycles with neutropenia in each genotype group, tC is the total number of chemotherapy cycles with neutropenia, and tN is the total number of patients with neutropenia.…”
Section: Data Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hepatic expression of UGT shows little interindividual variation, as opposed to the high interindividual variability found in the gastrointestinal tract (Strassburg et al, 1998(Strassburg et al, , 2000, further accentuated by the differential enzyme expression within different segments of the gastrointestinal tract (Strassburg et al, 1998(Strassburg et al, , 2000Antonio et al, 2003;Basu et al, 2004). Genetic polymorphisms have been described for several UGT, and some of them have been associated with interindividual variations in drug effect (Chung et al, 2005) and toxicity (Marsh and McLeod, 2004;Massacesi et al, 2006). Therefore, the identification of specific enzymes involved in the metabolism of a drug is important.…”
mentioning
confidence: 99%
“…Polymerase chain reactions (PCR) were conducted in a total volume of 50 μL containing 100 ng of genomic DNA, 25 pmoles of the UGT1A1 primer (UGT1A1 forward: 5′-GAT TTG AGT ATG AAA TTC CAG CCA G-3′ and UGT1A1 reverse: 5′-CCA GTG GCT GCC ATC CAC T-3′) [21] and the following reagents (obtained from Promega, Madison, WI): 0.1 mM each of dCTP, dGTP, dATP and dTTP; 2.5 mM of MgCl 2 ; 50 mM of potassium chloride; 10 mM of Tris (pH 9.0); 0.1 % Triton-X; and 2.5 U of Taq polymerase. After 35 cycles of amplification (denaturation at 94°C for 30 sec, annealing at 60°C for 1 min, and extension at 72°C for 1 min), the amplification products were electrophoresed in 3% agarose gel and visualized after staining with ethidium bromide.…”
Section: Methodsmentioning
confidence: 99%